Performance of concrete by using palm oil fuel ash (POFA) as a cement replacement material - Mohd Eriezhuan Effendie Shahrul, Rusli (2010)
Malaysia as the world's largest exporter of palm oil has been facing problem- in disposing palm oil fuel ash, a by-product of palm oil mill since many years ago. Through public concerns and research efforts, the agro waste by-product materials have potential to be utilized as construction material to replace conventional ordinary Portland cement (OPC). In this study, the effectiveness of agro waste ash by-product namely palm oil fuel ash (POFA) was developed as an alternative, materials to replace the OPC. POFA cement-based concrete is a concrete produced by integrating POFA as a pozzolan in concrete. The quality of POFA was improved by grinding until the median particle sizes were 50 microns. The unground and ground POFA were used to replace OPC by 0%, 10%, 20% and 30% by weight of cement binder. The compressive strength of POFA-concretes due to 7, 28, 60 and 90 days of curing ages were investigated. In addition, the durability resistance of POFA-concretes toward sulphate and acid solution also were assessed. The results revealed that the compressive strength of POFA-concretes was much lower than that of concrete without POFA. Conversely, the replacement of Portland cement by 20% of POFA recorded highest in strength compare to those POFA-concretes at 90 days. In case durability test, after being immersed in suphate solution for 90 days, the POFA-concretes with 30% of POFA had reduce expansion level compare to both of mixture. It is revealed that ground POFA is an excellent pozzolanic material and can be used as an alternative cement replacement in concrete. It is recommended that the optimum replacement levels of OPC by POFA are 30% and 20% mixture for a good strength in compressive test.